Molecular characterization of a rare G3P[3] human rotavirus reassortant strain reveals evidence for multiple human-animal interspecies transmissions - Pattara Khamrin (2018)
An unusual strain of human rotavirus G3P[3] (CMH222), bearing simian-like VP7 and caprine-like VP4 genes, was isolated from a 2-year-old child patient during the epidemiological survey of rotavirus in Chiang Mai, Thailand in 2000-2001. The rotavirus strain was characterized by molecular analysis of its VP4, VP6, VP7, and NSP4 gene segments. The VP4 sequence of CMH222 shared the greatest homology with those of caprine P[3] (GRV strain) at 90.6% nucleotide and 96.4% amino acid sequence identities. Interestingly, the VP7 sequence revealed highest identity with those of simian G3 rotavirus (RRV strain) at 88% nucleotide and 98.1% amino acid sequence identities. In contrast, percent sequence identities of both the VP4 and VP7 genes were lower when compared with those of human rotavirus G3P[3] reference strains (Ro1845 and HCR3). Analyses of VP6 and NSP4 sequences showed a close relationship with simian VP6 SG I and caprine NSP4 genotype C, respectively. Phylogenetic analysis of VP4, VP6, VP7, and NSP4 genes of CMH222 revealed a common evolutionary lineage with simian and caprine rotavirus strains. These findings strongly suggest multiple interspecies transmission events of rotavirus strains among caprine, simian, and human in nature and provide convincing evidence that evolution of human rotaviruses is tightly intermingled with the evolution of animal rotaviruses. © 2006 Wiley-Liss, Inc.